Pop-up peekaboo! meow! - Sirett, Dawn; Calver, Susan (London : Dorling Kindersley, 2012, 2012)
Suitable for developing imagination, early-thinking and memory skills, this book includes lift-the-flap, pop-out surprises, that your child can love to learn about Kitty Cat and her missing animal friends
English Stories
14
NEW
Keywords: Kittens -- Juvenile literature; Kittens; Toy and movable books -- Specimens; Toy and movable books